Management of Inclusive Education: Insights from SD Plus Darul Ulum, Indonesia - Zulfikar, Afifa Syamsun (FKIP Universitas Lampung, 2024)
Abstract: Management of Inclusive Education: Insights from SD Plus Darul Ulum Elementary School in Indonesia. Objectives: This study investigates SD Plus Darul Ulum, an Indonesian elementary school, examining its management of inclusive education, interactions, and socialization for special needs children. Methods: Using qualitative methods, data was collected through observations and interviews with key stakeholders, including teachers, administrators, parents, and students, then thematically analyzed. Findings: Findings reveal SD Plus Darul Ulum's strengths in engagement, student-centered learning, collaboration, diversity appreciation, and supportive physical environment. Teachers adapt methods, utilize diverse resources, and employ flexible assessments, while collaboration involves professionals, parents, and support staff to tailor strategies. The school prioritizes a physically accessible environment, employing Universal Design for Learning principles and assistive technologies. Conclusion: In conclusion, SD Plus Darul Ulum's commitment to inclusive education is deeply rooted in theories such as Universal Design for Learning, Differentiated Instruction, Social Constructivism, and Inclusive Education Principles. Keywords: inclusive education, special needs, elementary school, management strategies.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202416